Exosome loaded hydroxyapatite (HA) scaffold promotes bone regeneration in calvarial defect: an in vivo study - Youseflee, Pouya; Ranjbar, Faezeh Esmaeili; Bahraminasab, Marjan; Ghanbari, Ali; Faradonbeh, Davood Rabiei; Arab, Samaneh; Alizadeh, Akram; Nooshabadi, Vajihe Taghdiri (Cell and tissue banking, 2023)
In this study, hydroxyapatite (HA) scaffolds were synthesized and characterized, following the osteogenic and angiogenic effects of HA scaffolds with or without endometrial mesenchymal stem stromal cells (hEnSCs) derived Exosomes were investigated in rat animal model with calvaria defect. The X-ray diffraction (XRD) analysis of HA powder formation was confirmed with Joint Corporation of Powder Diffraction Standards (JCPDS) files numbers of 34-0010 and 24-0033A and Ball mill, and sintering manufactured Nano-size particles. Obtained results containing FE-SEM images presented that the surface of scaffolds has a rough and porous structure, which makes them ideal and appropriate for tissue engineering. Additionally, the XRD showed that these scaffolds exhibited a crystallized structure without undergoing phase transformation; meanwhile, manufactured scaffolds consistently release exosomes; moreover, in vivo findings containing hematoxylin–eosin staining, immunohistochemistry, Masson's trichrome staining, and histomorphometric analysis confirmed that our implant has an osteogenic and angiogenic characteristic. So prepared scaffolds containing exosomes can be proposed as a promising substitute in tissue engineering.